Деривационно-ассоциативная детерминанта как источник развития языка (на материале наружной рекламы и СМИ) - Араева, Людмила (Studia Rossica Posnaniensia, 2015)
Language is the result of the derivation process that takes place at all its levels, including spelling, punctuation and type subsystems. The stereotypes that are deeply rooted in the linguistic consciousness cause the potential possibilities of language to come into being based on apperception, i.e. the associative comprehension of language facts, both those long-established ones and those that have only recently manifested themselves in language forms.